2016
DOI: 10.1186/s40064-016-2952-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various acute hypoxic conditions on metabolic parameters and cardiac function during exercise and recovery

Abstract: PurposeEvaluation of metabolic parameters and cardiac function is important to determine the decrease in aerobic exercise capacity under hypoxic conditions. However, the variations in metabolic parameters and cardiac function and the reasons for the decrease in aerobic exercise capacity under hypoxic conditions have not been clearly explained. The purpose of this study was to compare the responses between sea level and various acute normobaric hypoxic conditions on metabolic parameters and cardiac function dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 27 publications
5
28
1
Order By: Relevance
“…Corroborating the results of Moon et al [31], we observed no significant difference in VO 2 between hypoxic and normoxic conditions during submaximal exercise; this is likely because the exercise intensity was fixed at a constant level across simulated environment conditions, resulting in the expenditure of same amount of energy. In addition, Hill et al [35] and Mazzeo [36] reported that the lack of difference in VO 2 during submaximal exercise between both environmental conditions is due to an increase in VE, HR, and CO because of acute hypoxic conditions.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Corroborating the results of Moon et al [31], we observed no significant difference in VO 2 between hypoxic and normoxic conditions during submaximal exercise; this is likely because the exercise intensity was fixed at a constant level across simulated environment conditions, resulting in the expenditure of same amount of energy. In addition, Hill et al [35] and Mazzeo [36] reported that the lack of difference in VO 2 during submaximal exercise between both environmental conditions is due to an increase in VE, HR, and CO because of acute hypoxic conditions.…”
Section: Discussionsupporting
confidence: 84%
“…Hypoxic conditions reduce arterial oxygen saturation, which is more affected during exercise due to increased pulmonary blood flow, which limits gas exchange at the alveoli [30]. Exercise under hypoxic conditions results in higher VE and HR than similar workloads performed under normoxic conditions; this finding might be attributed to the need to maintain O 2 perfusion [31]. However, these physiological adjustments are limited by the decrease in VO 2 max at high altitudes [32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations